Institutions and development: a view from below - Rohini Pande; Christopher Udry (Yale University, Economic Growth Center, 2005)
In this paper we argue the case for greater exploitation of synergies between research on specific institutions based on micro-data and the big questions posed by the institutions and growth literature. To date, the macroeconomic literature on institutions and growth has largely relied on cross-country regression evidence. This has provided compelling evidence for a causal link between a cluster of 'good' institutions and more rapid long run growth. However, an inability to disentangle the effects of specific institutional channels on growth or to understand the impact of institutional change on growth will limit further progress using a cross-country empirical strategy. We suggest two research programs based on micro-data that have significant potential. The first uses policy-induced variation in specific institutions within countries to understand how these institutions influence economic activity. The second exploits the fact that the incentives provided by a given institutional context often vary with individuals' economic and political status. This can help us better understand how institutional change arises in response to changing economic and demographic pressures.
Keywords: O11; O12; O17; P51; 330; Institutions; growth; cross-country regressions